Undocumented Patients in the Emergency Department: Challenges and Opportunities - Shamsher Samra; Breena R. Taira; Erika Pinheiro; Rebecca Trotzky-Sirr; Todd Schneberk (Western Journal of Emergency Medicine, 2019)
In the United States, undocumented residents face unique barriers to healthcare access that render them disproportionately dependent on the emergency department (ED) for care. Consequently, ED providers are integral to the health of this vulnerable population. Yet special considerations, both clinical and social, generally fall outside the purview of the emergency medicine curriculum. This paper serves as a primer on caring for undocumented patients in the ED, includes a conceptual framework for immigration as a social determinant of health, reviews unique clinical considerations, and finally suggests a blueprint for immigration-informed emergency care.